2014
DOI: 10.1002/alr.21274
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D deficiency upon clinical presentation in nasal polyposis

Abstract: VD3 insufficiency/deficiency is common in CRSwNP patients, especially those of African American race. Lower levels of VD3 are associated with worse LMS on CT. The role of VD3 in CRSwNP warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 13 publications
6
56
0
1
Order By: Relevance
“…25VD 3 was inversely related to LM score, consistent with U.S. patients. 432 With regard to allergic status, Ozkara et al 897 found Turkish patients with concurrent CRSwNP and AR had significantly lower 1,25VD 3 than healthy controls. This effect was not seen in CRSwNP without AR, implying that allergy is a necessary condition.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%
See 2 more Smart Citations
“…25VD 3 was inversely related to LM score, consistent with U.S. patients. 432 With regard to allergic status, Ozkara et al 897 found Turkish patients with concurrent CRSwNP and AR had significantly lower 1,25VD 3 than healthy controls. This effect was not seen in CRSwNP without AR, implying that allergy is a necessary condition.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%
“…This work may partly explain the inverse correlation between 25VD 3 levels and bone erosion noted in some clinical studies. 426,432,433 Two statements can be made about VD 3 in CRSsNP:…”
Section: S55mentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D derivatives can prevent human nasal polyp-derived fibroblast proliferation in cultured cell models, and regulated on activation normal T cell-expressed and -secreted (RANTES) and matrix metalloproteinase 9 produced in keratinocytes and interleukin-8 production in normal human dermal fibroblasts [2527]. Some recent studies indicated that vitamin D deficiency is related to disease severity and might be a key player in the etiopathology of chronic rhinosinusitis with NP [2830]. Hu et al reported that polymorphisms in CYP2R1-rs10766197 and DHCR7/NADSYN1-rs12785878 are associated with vitamin D deficiency in Uygur and Kazak ethnic populations [31].…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of plasma vitamin D 3 have been reported in both adults and children with CRSwNP and allergic fungal rhinosinusitis compared with CRSsNP patients and controls [39,41]. Lower levels of vitamin D 3 have been associated with increased values of the Lund-Mackay CT score in patients with CRSwNP [42].…”
Section: Nutrition Habits and Occupational Factorsmentioning
confidence: 97%